Occupational patterns of families living with a health condition: A scoping review. (3rd October 2021) - Ranger, Marie-Christine; Bossé, Stéphanie; Martini, Rose
Abstract: Background: A family's health is sustained by its occupational patterns. While it is commonly accepted that a health condition places extra demands on a family's time or can limit daily occupations, few studies have reported on the occupational patterns of these families. Aims/objectives: This scoping review provides an overview of the current state of research exploring occupational patterns of families living with a health condition. Material and method: Publications between 2000 and 2018 indexed in CINAHL, PsycInfo, Medline and Scopus databases were searched. Results: Seventy-seven studies were included in the final content analysis. Findings suggest that families' occupational patterns are more complex than simply the sum of individual and shared occupational patterns, but consist of interconnected relational aspects of occupations, rarely highlighted in studies. Moreover, testimonies tend to be predominantly from the mother's perspectives, thereby limiting the scope of understanding of the interdependent nature of families' occupational patterns. Conclusion: To better understand the complexity and interdependence of families' occupational patterns, future studies should examine multiple perspectives (parents and children) when studying occupations in a family setting. This can be enabled by the use of a variety of data collection methodologies.